2011
DOI: 10.4097/kjae.2011.61.6.488
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ramosetron's and ondansetron's preventive anti-emetic effects in highly susceptible patients undergoing abdominal hysterectomy

Abstract: BackgroundThis study compared the preventive effects of ramosetron and ondansetron on postoperative nausea and vomiting (PONV) in highly susceptible patients undergoing abdominal hysterectomy.MethodsIn a prospective, randomized, double-blinded study, a total of 120 highly susceptible women (nonsmokers, those receiving opioid-based IV patient-controlled analgesia [PCA]) undergoing abdominal hysterectomy were included in the study. Patients were divided into 2 groups and each group received either 0.3 mg of ramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…[10] Many of the recent studies have shown that ramosetron is more effective than ondansetron in preventing PONV for the patients undergoing various other surgeries. [8111213] Furthermore, antiemetic efficacy of combination of ramosetron and dexamethasone was found to be similar to that of ondansetron and dexamethasone, when used as prophylaxis for the spine surgeries. [14] Addition of dexamethasone did not provide any advantage to ramosetron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Many of the recent studies have shown that ramosetron is more effective than ondansetron in preventing PONV for the patients undergoing various other surgeries. [8111213] Furthermore, antiemetic efficacy of combination of ramosetron and dexamethasone was found to be similar to that of ondansetron and dexamethasone, when used as prophylaxis for the spine surgeries. [14] Addition of dexamethasone did not provide any advantage to ramosetron.…”
Section: Discussionmentioning
confidence: 99%
“…[67] The newer 5-HT3 antagonist ramosetron, with long duration of action, has been found to be more effective than ondansetron in reducing the early as well as delayed PONV, when used in other surgeries. [8]…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that this class of antiemetics exhibited better prophylactic efficacies compared with the older traditional drugs including droperidol, perphenazine, or metoclopramide [5-7]. A number of studies have been conducted to compare the prophylactic antiemetic efficacies among 5-HT 3 receptor antagonists [8-12]. To date, however, there are few clinical studies comparing the prophylactic efficacies of ondansetron, ramosetron, and palonosetron in high-risk patients with PONV.…”
Section: Introductionmentioning
confidence: 99%
“…The precise antiemetic mechanism of ramosetron remains unclear, but it may act on sites containing receptors that have demonstrated antiemetic effects [18]. Many studies have examined the prophylactic antiemetic effects of ramosetron compared with other 5-HT3 receptor antagonists including ondansetron and granisetron [21,22]. Choi et al [6] concluded that ramosetron 0.…”
Section: Resultsmentioning
confidence: 99%